ISOMETRIC HANDGRIP EXERCISE TERHADAP TEKANAN DARAH DAN NADI PADA HIPERTENSI : LITERATURE REVIEW - Widiastuti, Agung; Ulkhasanah, Muzaroah Ermawati; Irawan, Ady (Coping: Community of Publishing in Nursing; Vol 9 No 6 (2021): Desember 2021, 2021)
Background: Hypertension is still a health problem in the world. Hypertension if not controlled will lead to long-lasting complications and can be fatal such as heart failure, kidney failure and even stroke which can have an impact on a person's quality of life. Seeing this phenomenon requires both pharmacological and non-pharmacological handling. Objective: This study conducted a systematic review of isometric handgrip exercise on blood pressure and pulse in hypertensive patients. Methods: Searching for articles using a search strategy through the database, namely Pubmed, Ebsco, Google schoolar, Scientdirect using the keywords: Isometric Handgrip Exercise AND Blood pressure AND Hypertention, articles were analyzed according to inclusion and exclusion criteria. Results: The data used are 8 international articles. Based on the results of the review, giving isometric handgrip exercises can produce a decrease in blood pressure and pulse. Conclusion: Giving isometric handgrip exercise if done regularly can reduce the risk of developing hypertension in the future .